Revisiting the export-growth nexus for India: an empirical exercise. (6th October 2020) - Dixit, Vikas; Parveen, Shaista
This paper attempts to investigate empirically the export-growth nexus for India from different theoretical perspectives. Using robust time series techniques, and considering both demand-side and supply-side explanations of the relationship between export and output growth, this paper finds empirical support for export-led growth hypothesis for India for long run and short run from supply-side as well as demand-side perspectives. The demand-side orientation appears to be the better explanation of this relationship during post-liberalisation period. The horizontal export diversification is observed to have U-shaped relationship with output growth. In terms of export composition (or vertical export diversification), share of manufactured exports bear a positive and significant relation with output growth, whereas the positive but insignificant impact of services exports on economic growth underlines the need for a rigorous policy action in this sector. The results of empirical estimation are further confirmed by lag-augmented vector autoregressive non-causality test.